Application of 3D-printed osteotomy guides in periacetabular osteotomy: A short-term clinical study. Issue 11 (November 2022) - Ma, Shiqiang; Xiao, Li; Guo, Donghui; Shi, Qiuling; Shen, Runbin; Li, Xiaoming
Objective: To compare the clinical efficacy between personalised 3-dimensional (3D) printed osteotomy and traditional osteotomy in periacetabular osteotomy (PAO). Methods: Twenty-two patients with acetabular dysplasia were randomly divided into a personalised 3D-printed osteotomy group and a traditional osteotomy group without 3D printing assistance. The operation time, intraoperative blood loss, X-ray frequency, quantity of postoperative drainage, postoperative transfusion rate, hip angle and Harris hip score of 6 months postoperative were studied and compared to evaluate the surgical efficacy between personalised 3D-printed osteotomy and traditional osteotomy in periacetabular osteotomy. Results: The operation time, intraoperative blood loss, X-ray frequency, postoperative 24 h drainage volume in the personalised 3D-printed osteotomy group (114.70 ± 2.21 min, 639.70 ± 5.00 mL, 11.82 ± 0.42 times, 231.20 ± 3.86 mL) was superior to the traditional group (150.40 ± 2.45 min, 850.50 ± 5.34 mL, 17.09 ± 0.39 times, 324.30 ± 4.06 mL). There was a statistically significant difference between the 3D-printed osteotomy group and the traditional osteotomy group in terms of the operation time, intraoperative blood loss, X-ray frequency and postoperative 24 h drainage volume ( p  < 0.05). And there were no substantial differences in the hip angle and the 6-month postoperative Harris hip score between the two groups ( p  > 0.05). Conclusion: The 3D-printed osteotomy template for PAO is a valid method and its short-term clinical effect is superior to that of traditional osteotomy.